Family planning among undergraduate university students: a CASE study of a public university in Ghana - Fred Yao Gbagbo; Jacqueline Nkrumah (BMC, 2019)
Abstract Background Globally, the rate of unplanned pregnancies among students at institutions of higher education, continue to increase annually despite the universal awareness and availability of contraceptives to the general population. This study examined family planning among undergraduate university students focusing on their knowledge, use and attitudes towards contraception in the University of Education Winneba. Methods The study was a descriptive cross-sectional survey using a structured self-administered questionnaire. One hundred undergraduate students from the University of Education Winneba were selected using a multistage simple random sampling technique. A Likert scale was used to assess the attitude of the respondents towards family planning methods. Results Findings show that the respondents had a positive attitude towards family planning with an average mean score of about 4.0 using a contraceptive attitude Likert scale. Knowledge of contraception, awareness and benefits however do not commensurate contraceptive use among undergraduate students since availability, accessibility and preference influence usage. Emergency Contraception (Lydia) was reported as easy to get contraceptive, hence the most frequently used contraceptive (31%) among young female students aged 21-24 years who appeared as the most vulnerable in accessing and using contraceptives due to perceived social stigma. Conclusion The observation that levels of Family Planning awareness levels do not commensurate knowledge and usage levels calls for more innovative strategies for contraceptive promotion, and Education on the various university campus. The study recommends that public Universities in Ghana should consider a possible curriculum restructuring to incorporate family planning updates. In this regard, a nationwide mixed method study targeting other tertiary institutions including colleges of education in Ghana is required to explore the topic further to inform policy and programme decisions.